Longitudinal cohort study of childhood IQ and survival up to age 76 - Whalley, Lawrence J (BMJ, 2001)
OBJECTIVES: To test the association between childhood IQ and mortality over the normal human lifespan. DESIGN: Longitudinal cohort study. SETTING: Aberdeen. SUBJECTS: All 2792 children in Aberdeen born in 1921 and attending school on 1 June 1932 who sat a mental ability test as part of the Scottish mental survey 1932. MAIN OUTCOME MEASURE: Survival at 1 January 1997. RESULTS: 79.9% (2230) of the sample was traced. Childhood mental ability was positively related to survival to age 76 years in women (P<0.0001) and men (P<0.0001). A 15 point disadvantage in mental ability at age 11 conferred a relative risk of 0.79 of being alive 65 years later (95% confidence interval 0.75 to 0.84); a 30 point disadvantage reduced this to 0.63 (0.56 to 0.71). However, men who died during active service in the second world war had a relatively high IQ. Overcrowding in the school catchment area was weakly related to death. Controlling for this factor did not alter the association between mental ability and mortality. CONCLUSION: Childhood mental ability is a significant factor among the variables that predict age at death.